Measuring the Quality of Life Level of Secondary School Teachers: A Field Study in the Secondary Schools of El Azizia, Médéa - chanane, yasmina; lamine, nassira (El Omda in Linguistics and Discourse Analysis, 2025)
The current study aims to measure the quality of life of the secondary education teachers at the secondary schools of Al-Azizia Department in Medea, as well as to identify the differences in the quality of life of the sample members according to the gender variable (male, female), and also to years of experience (from 01 to 05 years, from 06 Up to 10 years, more than 10 years). In order to achieve the objectives of the study, a sample of (120) secondary education teachers in the secondary schools of Al-Azizia Department were selected by (60) males and (60) females. The descriptive approach was adopted in this study and the quality of life measure prepared by Al-Kubaisi in the academic year (2010-2011) was used as a study tool. The statistical methods used were the frequencies, percentages, Cronbach's alpha, arithmetic averages, standard deviations, the “T” test for a sample and a population, the “T” test for two independent samples and the single-sample analysis of variance. A set of results were reached, which they were as follows: - Secondary education teachers teaching in Azizia high schools expressed an excellent level of quality of life. - The statistical significance indicated that there were no differences related to the gender variable (male, female) for secondary education teachers working in Azizia high schools in the level of their response on the quality of life scale. - In addition, the years of experience (01 to 05 years, 06 to 10 years, more than 10 years) of secondary education teachers working in Azizia secondary schools did not show any statistically significant effect on their performance on the quality of life scale. In the light of the obtained results, a number of recommendations were proposed.